Penguatan Kesadaran Multikultural Perspektif Neurosains melalui Edukasi Budaya Pemberian Nama Anak pada Masyarakat Jawa di Baleharjo, Pacitan - Riyanto, Ridho (INKAMKU : Journal of Community Service, 2024)
Strengthening multicultural awareness at the village community level is increasingly important amid shifts in cultural identity caused by modernization. This community service program was conducted in Baleharjo Village, Pacitan Regency, focusing on cultural education regarding child naming traditions from a neuroscience perspective. The topic was selected because naming traditions in Javanese culture contain philosophical and multicultural values that can reinforce empathy and social identity, yet their meanings are gradually diminishing. The method employed was Participatory Action Research (PAR) based on Community Based Research, including initial assessment, interactive workshops, narrative reflection, and pre–post evaluation using a Likert scale. The results demonstrated significant improvements in participants’ philosophical understanding of names, multicultural awareness, and social empathy, exceeding a 25% increase from baseline scores. These findings indicate that integrating local wisdom and neuroscience perspectives is effective in fostering community-based multicultural awareness and has strong potential for replication in similar socio-cultural contexts.